2006
DOI: 10.1093/annonc/mdl167
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of nephroblastoma in a developing country

Abstract: Morbidity and mortality with nephroblastoma is high in our environment. Late presentation, poverty, ignorance and poor compliance to treatment constitute a great challenge to the paediatric oncologist in a developing country. Solutions may lie in improving health funding and health information in the health care delivery system. Free health care for children with malignancy is advocated. Collaboration with institutions in the privileged parts of the world may help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 8 publications
9
67
3
1
Order By: Relevance
“…The interval between the end of preoperative chemotherapy and surgery, and between surgery and the start of postoperative therapy was not respected because the surgeon was not available or because the pathology report was not available. This situation, which is unknown or rare in developed countries, has to be compared to those described in other African countries which have, to various degrees, similar socio-economic problems [12,13]. The absence of radiotherapy for selected patients less than 3 years of age, with a small stage III tumor, initially treated by surgery, did not seem to influence the prognosis for this tiny minority [17].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The interval between the end of preoperative chemotherapy and surgery, and between surgery and the start of postoperative therapy was not respected because the surgeon was not available or because the pathology report was not available. This situation, which is unknown or rare in developed countries, has to be compared to those described in other African countries which have, to various degrees, similar socio-economic problems [12,13]. The absence of radiotherapy for selected patients less than 3 years of age, with a small stage III tumor, initially treated by surgery, did not seem to influence the prognosis for this tiny minority [17].…”
Section: Discussionmentioning
confidence: 89%
“…The SIOP studies demonstrated the value of preoperative chemotherapy [3] to limit the risk of tumor rupture during surgery, to increase the percentage of stage I tumors requiring less aggressive treatments and to limit complications associated with surgery [9]. In Africa, the results of such treatment management are fragmentary [10][11][12][13] or are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This assertion can be corroborated by studies done in the sub-Saharan Africa by Ekense et al [2,3] which showed that Wilms' tumour is the most common childhood malignancy in Sub-Saharan Africa. Despite being a malignant tumour, a survival rate of over 90% is now seen today (compared to 30% in the thirties) and this is an evidence of the success of collaborative trials and the use of multimodal therapy [4][5][6].…”
Section: Introductionmentioning
confidence: 61%
“…Most of the tumours weighed between 501-1000 grams representing (40.9%) while 27.3% of the tumour weighed between 1001-1500 grams (Table 1). In terms of tumour volume, majority fell between 1001-2000 cm 3 accounting for (40.9%). Necrosis was observed in 95.5% of the cases.…”
Section: Resultsmentioning
confidence: 99%
“…It is mainly a childhood cancer, even though it occurs in adults occasionally. In Kenya, Nephroblastoma accounts for 3.3% of childhood cancers [2,3,4,5]. This is a lower incidence than in Western countries where it accounts for up to 8% of childhood cancers [6].…”
Section: Introductionmentioning
confidence: 99%